The Skandapurāṇa, Volume V: Adhyāyas 96-112 : The Varāha Cycle and the Andhaka Cycle continued - Bisschop, Peter Christiaan; Yokochi, Yūko; Dokter-Mersch, Sanne; Törzsök, Judit (Groningen Oriental Studies, Supplement, 2021)
Skandapurāṇa V presents a critical edition of Adhyāya s 92-112 from the Skandapurāṇa , with an introduction and annotated English synopsis. The text edited in this volume includes the extensive myth of Viṣṇu's manifestation as the Boar (Varāha), who conquers Hiraṇyākṣa and wins back the Earth for the gods; its aftermath, which involves the birth of Varāha's son Vṛka and Skanda's finishing of Viṣṇu's Boar manifestation; Devī's instructions to the goddesses about donations, fasts and penances; and the continuation of the Andhaka cycle. The introduction addresses the incorporation of Vaiṣṇava mythology in the text, the composition and revision of Adhyāya 112 in the different recensions, and the Dharmanibandha citations of Devī's teachings